Giant Cell Tumor of the Metacarpal and Its Intervention to Preserve Joint Function: A Case Report - Ericsen Tiondi Putra; Kusuma, Yudha Eka; Calvin, Calvin (Indonesian Journal of Medicine, 2025)
Background: Giant cell tumor (GCT) is one of the most common benign bone tumors, but it has a high recurrence rate and is aggressive. It can occur elsewhere, but frequently in the distal femur and proximal tibia. The goal of treatment is to remove the tumor cells and maintain the metacarpophalangeal function. Various modalities exist to remove the tumor cells from curettage, wide excision, radical excision, or amputation. Reconstruction following the removal of tumor cells also varied by using graft, bone cement, prosthesis, or arthrodesis. There are no definitive guidelines to determine which modalities are the best, especially in unusual sites. In this case report, we present an unusual site of GCT in the second metacarpal, and clinical outcomes after the 1-year final follow-up were nearly normal. Case Presentation: A 22-year-old female presented to the hospital with a history of a lump and intermittent pain in the right hand for 2 years. Physical examination and radiograph suspected an unusual site of GCT and no cartilage involvement. A core biopsy was taken, and a GCT was confirmed. Wide excision, preserving the native joint of the metacarpal, and reconstruction using autologous non-vascularized fibular graft with the help of K-wire and adjuvant of hydrogen peroxide. Results: Constant improvement of clinical outcomes post-operatively with Michigan Hand Outcomes Questionnaire (MHQ) score was nearly normal, and there was no sign of recurrence at 6-month follow-up. Conclusion: Our report suggests that wide excision and reconstruction by fibular struts with a preserved native metacarpal joint, followed by hydrogen peroxide as an adjuvant and K-wire as a fixator, could be used as a combination therapy with good results.